1977
DOI: 10.1002/path.1711220102
|View full text |Cite
|
Sign up to set email alerts
|

Histological criteria for immunological rejection of mouse skin homografts

Abstract: The sequence of events in homograft rejection of skin in mice was studied by light microscopy in comparison to the reactions to isografts. Male C3H mice were used as donors and Balb/c mice were the recipients. In non-infected grafts no invasion of graft tissue by inflammatory cells occurred except for the marginal areas bordering on the graft bed. The most constant feature of immunological rejection was occlusion of blood vessels at the graft-host border with ischaemia of the graft. This indicated that skin ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1978
1978
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
(11 reference statements)
1
2
0
Order By: Relevance
“…6 D). These data are consistent with the findings of Wolman et al ( 45 ) who reported that skin allograft rejection in BALB/c hosts reflects occlusion of blood vessels at the graft-host border with ischemia of the graft. Unlike islet allografts, skin allografts are highly vulnerable to CD4-mediated rejection ( 1 , 2 ); moreover, A/J donors are fully mismatched from BALB/c at MHC class II alleles (I-A k and I-E k ).…”
Section: Discussionsupporting
confidence: 93%
“…6 D). These data are consistent with the findings of Wolman et al ( 45 ) who reported that skin allograft rejection in BALB/c hosts reflects occlusion of blood vessels at the graft-host border with ischemia of the graft. Unlike islet allografts, skin allografts are highly vulnerable to CD4-mediated rejection ( 1 , 2 ); moreover, A/J donors are fully mismatched from BALB/c at MHC class II alleles (I-A k and I-E k ).…”
Section: Discussionsupporting
confidence: 93%
“…By contrast, Orai1 KI/KI mice showed significantly prolonged skin allograft survival with a median graft survival of 21.1 days. Five days after transplantation, skin grafted onto wildtype C57BL/6 mice in general showed more pronounced perivascular leukocyte infiltration and occlusion of blood vessels – criteria for rejection of skin allografts (30) – compared to Orai1 KI/KI recipient mice (Fig. 5B).…”
Section: Resultsmentioning
confidence: 98%
“…The animals used and the transplantation procedures were described in an earlier paper (Wolman, Bleiberg and Leibovici, 1976). The histological techniques were also identical .…”
Section: Methodsmentioning
confidence: 99%